Long-Term Follow-Up of Contrast-Induced Acute Kidney Injury: A Study from a Developing Country - Ashraf O. Oweis; Sameeha A. Alshelleh; Nesreen Saadeh; Mohamad I. Jarrah; Rasheed Ibdah; Karem H. Alzoubi (International Journal of Vascular Medicine)
Introduction. Contrast-induced acute kidney injury (CI-AKI) is a worldwide known complication related to the use of contrast media with either imaging or angiography; it carries its own complications and effect on both morbidity and mortality; early identification of patients at risk and addressing modifiable risk factors may help reducing risk for this disease and its complications. Methods. This was a prospective observational study, where all patients admitted for cardiac catheterization between June 2015 and January 2016 were evaluated for CI-AKI. There were two study groups: contrast-induced acute kidney injury (CI-AKI) group, and noncontrast-induced acute kidney injury (non-CI-AKI) group. Results. Patients (n=202) were included and followed up for 4 years. Death and development of chronic kidney disease (CKD) need for another revascularization were the end points. The incidence of CI-AKI was 14.8%.In univariate analysis, age (P=0.016) and serum albumin at admission (P=0.001) were statistically significant predictors of overall death. Age (P=0.002), HTN (P=0.002), DM (P=0.02), and the use of diuretics (P=0.001) had a statistically significant impact on eGFR. The rate of recatheterization was not statistically significant between the two groups (61 (35.5%) for the non-CI-AKI vs. 12 (40%) for the other group; P=0.63). Some inflammatory markers (NGAL P=0.06, IL-19 P=0.08) and serum albumin at admission P=0.07 had a trend toward a statistically significant impact on recatheterization. Death (P=0.66) and need for recatheterization (P=0.63) were not statistically different between the 2 groups, while the rate of eGFR decline in for the CI-AKI was significant (P=0.004). Conclusion. CI-AKI is a common complication post percutaneous catheterization (PCI), which may increase the risk for CKD, but not death or the need for recatheterization. Preventive measures must be taken early to decrease the morbidity.